0193 Alcohol and other drugs among workers: prevalence and job related consequences. (21st August 2017) - Lambrechts, Marie-Claire; Vandersmissen, Lieve; Godderis, Lode
Abstract : Few data on the use of alcohol and other drugs in workers and possible effects on job performance are available. In 2016 an anonymized questionnaire was distributed among Belgian employees while waiting for a periodical medical examination. AUDIT-C and One Single Questions were used to measure prevalence of substance use. Effects on absenteeism, lost productivity, workplace accidents, conflicts with co-workers and sanctions by employers respectively experienced by the workers and observed among colleagues were investigated. 5367 workers completed the questionnaires. 83% drank at least one standard unit in the 12 months preceding the survey; 7.5% had used cannabis or other illegal drugs, 9.3% hypnotics, 5.5% tranquillizers and 7.9% antidepressants; 11.3% took prescribed drugs for nonmedical reasons. 11.4% of current drinkers had an average consumption of 5 to 6 units a day, which was significantly higher among employees<35 year; 8.5% exhibited binge drinking at least once a week. 39.1% of last year drinkers had an indication of problem drinking and 12.2% experienced consequences on the job. 27.8% observed negative effects among their colleagues, especially being late at work (18.3%), irregular job performances (18%) and absenteeism (15.7%) Due to illicit drug use, 1.2% of the respondents experienced some negative effects on the job, 7.2% observed negative effects among their colleagues. Regarding the use of psychoactive medication, significantly more used by women, this was respectively 3% and 10.7%. As the negative impact of work related substance use, especially of alcohol, is obvious, a tailored and multicomponent alcohol and drug policy is appropriate.